2021
DOI: 10.1016/j.jsurg.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Use of 360° Video for a Virtual Operating Theatre Orientation for Medical Students

Abstract: Background Operating theatres are a unique learning environment that some learners find daunting. By employing orientations some of these fears can be reduced but these require operating theatre space and personnel and are not standardized. Methods We utilized a 360 ° camera to generate a “virtual” 360 ° video orientation. It was filmed in first-person perspective to improve engagement and to make it more experientia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…Still, in our literature review, we found a previous study that demonstrated use of the technique with demonstration of nursing and paramedic skills, where it was also looked upon favorably 14 . More so, there is ongoing interest and progression in mixed reality technology as a tool for medical education 15 . In considering this exciting educational immersive experience, our group sees the FP-POV tutorial video as a unique means of the learner immersing in the skill.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Still, in our literature review, we found a previous study that demonstrated use of the technique with demonstration of nursing and paramedic skills, where it was also looked upon favorably 14 . More so, there is ongoing interest and progression in mixed reality technology as a tool for medical education 15 . In considering this exciting educational immersive experience, our group sees the FP-POV tutorial video as a unique means of the learner immersing in the skill.…”
Section: Discussionmentioning
confidence: 93%
“…Video-based instruction has shown to improve knowledge retention and clinical skill 12,13 . Tutorial videos filmed from a first-person point of view (FP-POV) have also been well received by educators and trainees 14,15 . A FP-POV video is captured from the perspective of individual, simulating as if looking through their eyes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of the included 92 papers, 38% (35 paper) reported the integration of VS in surgical training for medical undergraduates, among which 12 studies focused on the instructional application of virtual endoscopic [including laparoscopic ( 31 , 36 , 37 , 56 , 73 , 76 , 78 , 98 ), arthroscopic ( 26 , 47 , 48 ), and otoscopic ( 53 )] simulators; 7 studies were for learning procedures or concepts of orthopedic and bone surgery ( 32 , 33 , 35 , 45 , 57 , 66 , 70 ); 5 studies were based on VS system or platform as a primary mode of teaching neurosurgical procedures, neuroanatomy and pathologies ( 22 , 28 , 71 , 80 , 81 ); 4 papers ( 38 , 61 , 75 , 84 ) reported the exposure of medical undergraduates as novice surgeons to the robotic surgery simulators; 2 studies conducted by the same team ( 64 , 65 ) explored the VR simulation-based training in Cochlear Implant surgery; the other 2 were for learning basic motor skills in liver surgery ( 50 , 52 ); 1 in minimally invasive surgery ( 97 ), and 1 in vitreoretinal surgery ( 67 ). In addition, Fukuta et al ( 46 ) generated a virtual operating theater orientation to improve knowledge and confidence of medical undergraduates. Except five validation studies of virtual simulators ( 26 , 47 , 53 , 65 , 81 ) in which the undergraduates acted as the novice group for comparison with the skilled group, the findings of all the other included studies positively supported the usability and its feasibility of integrating VS in surgical training.…”
Section: Resultsmentioning
confidence: 99%
“…As such, 360°VR has been labelled an appropriate “middle ground” between screen-based videos and VR, given it allows greater interaction with scanning the environment through head movements ( 19 ). 360°VR has been investigated as an authentic educational tool in teacher education ( 20 , 21 ); environmental conservation ( 22 ); medical and surgical training ( 23 ); safety management ( 24 ); and inter-professional communication in healthcare ( 25 ). The use of this technology has grown in recent years (see Pirker and Dengel ( 26 ) for a review).…”
Section: °Vr As An Authentic Learning Toolmentioning
confidence: 99%